PERCEPTION OF MBBS AND BDS INTERNS OF CHITWAN REGARDING THEIR CLINICAL POSTING DURING COVID-19 PANDEMIC - Banstola , Prabesh; Shah , Nehal Kumar; Bhattarai , Rosina (Journal of Chitwan Medical College, 2022)
Background: COVID-19 pandemic has changed the routines throughout the world where medical sector hasn’t remained untouched. Medical interns have been the vulnerable population being affected by the pandemic. The pandemic has created a huge impact psychologically and academically on the medical students. This study was conducted in the medical colleges of Chitwan, Nepal aiming to find out the perception of the MBBS and BDS interns regarding their clinical posting during COVID-19 pandemic. Methods: A descriptive cross-sectional study was conducted among MBBS and BDS interns of medical colleges in Chitwan, Nepal. A structured 14 item questionnaire containing demographics (4 items) and perceptions on safety, satisfaction and confidence (10 items) regarding COVID-19 pandemic was used for online survey via email. Consent was taken for the survey and descriptive study was done. Data entry was done in Microsoft Excel and analysis is SPSS 16. Descriptive statistics was done. Results: The questionnaire was sent to 130 interns at Chitwan out of which 68 interns responded among which 29.4 % were BDS interns and 70.6 % were MBBS interns. Majority of the interns didn’t feel safe to do duty in their internship and also feared of transmission of COVID-19 through them to their families. They also didn’t have adequate confidence for the patient management due to the type of learning exposure during the pandemic. Conclusions: The study revealed that virtual learning isn’t effective for the interns for the patient management. Majority of the interns at Chitwan didn’t feel safe to do clinical duty during the pandemic.